Effects of arbuscular mycorrhizal fungi, rhizobium and phosphorus on mungbean (Vigna radiata) in saline soil - Rahman, M; Hossain, MA; Ali, ME; Anik, MFA; Alam, F (Bangladesh Journal of Agricultural Research, 2019)
A pot experiment was carried out in the nethouse of Soil Science Division of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur in 2017 and 2018 with an objective to evaluate the potentiality of AM fungi, Rhizobium and P in different best combinations on germination (%), growth, yield and yield contributing characters, nodulation, sporulation and nutrient concentration of mungbean under low salinity (4 dSm-1) stress condition. The experiment was designed in CRD with 10 treatments and 4 replications. Mungbean variety BARI Mung-6 was used as a test crop. Peat based rhizobial inoculum (BARI RVr-403) was used in this experiment @ 50 g kg-1 seed and the population density of inoculum being above 108 cfu g-1 inoculant. Soil based AM inoculum containing 275 ± 20 spores and infected root pieces of the host plant was used in each pot. There were 10 treatments viz. T1: Control (Not absolute control), T2: Arbuscular mycorrhiza (AM) + 50% P, T3: AM + 75% P, T4: AM + 100% P, T5: Rhizobium + 50% P, T6: Rhizobium + 75% P, T7: Rhizobium + 100% P, T8: AM + Rhizobium + 50% P, T9: AM + Rhizobium + 75% P and T10: AM + Rhizobium + 100% P. The highest seed yield (2.28 g plant-1, 46.2% higher over control in 2017 and 2.97 g plant-1, 33.8% higher over control in 2018) and stover yield (5.23 g plant-1, 30.8% higher over control in 2017 and 5.67 g plant-1, 32.8% higher over control in 2018) were found in AM + Rhizobium + 75% P treatment. Dual inoculation significantly increased P, S, Mg, Fe, Mn and Zn concentration of mungbean plant compared to control. The results suggest that inoculation of AM fungi and Rhizobium along with 75% of recommended P rate can help increased mungbean yield under low salinity stress condition through influence on nodulation, colonization and nutrient uptake. Bangladesh J. Agril. Res. 44(1): 153-165, March 2019